Climate changes and their repercussions on food security in Iraq - Shaker Maatouq, Prof. Dr. Safia (Basra studies journal, 2024)
The study examined the impact of climate changes on the extent of achieving food security in Iraq, as the phenomenon of climate change posed a major threat to large areas of land resulting from the unsustainable exploitation of natural resources by humans. The research aimed to identify the reality of the phenomenon of climate change in Iraq as it is a region characterized by a climate It is semi-arid and sheds light on the extent to which Iraq is affected by these changes due to wars, pollution, drought and other environmental impacts. The results of this study showed that there is a clear climate change in most climate elements that has led to an increase in the general average temperatures as well as in the frequency of dust storms. And increasing daily levels of suspended particles, as well as environmental pollution. The exposure of large areas of land to deterioration directly contributed to the increase in the area of ​​desertified lands threatened by drought and the loss of huge amounts of the surface layer due to the deterioration of vegetation cover, to soil deterioration and disintegration, land degradation and its repercussions on agricultural activity in Iraq and the resulting effects on food security and studying the reasons for the decline and decrease in Agricultural productivity to a level that does not meet the needs of local demand for it, and what are the implications of the inability of local production to meet the population’s requirements on food security and self-sufficiency. In Iraq, there was and still is an urgent need to develop and develop agricultural productivity, especially the production of strategic crops, As one of the most important crops in the food security system, in order to secure the increasing demand for foodstuffs resulting from the increase in the population and the rise in their standard of living, and thus achieve food security.